Development of a model of nursing education grounded in caring and application to online nursing education. - Purnell MJ (International Journal for Human Caring, 2006)
This paper describes an innovative model for nursing education grounded in caring (MONEC). Based on nursing theory, the model and its online application in nursing education is supported by both the nursing and interdisciplinary research. Part I de-scribes model underpinnings of the theory of, nursing as caring, the dance of caring persons as organizing pedagogy, and intentionality in nursing as transformative in aesthetic knowing. Part II describes an application of the model in creation of an online course and challenges in developing a unique, aesthetically wallpapered environment. Student responses to the environment are presented and implications for research and education are discussed.